THE INFLUENCE OF THE EUROPEAN UNION ON COMBATING IRREGULAR MIGRATION IN THE REPUBLIC OF SERBIA - Cvetković, Nenad; Обрадовић, Зоран (The Policy of National Security, 2024)
The European Union has been leading a common policy in combating irregular migration for many years. It is based on the comprehensive cooperation of all actors involved in population migration and, above all, with the countries of origin, transition and final destination of migrants. In the process of joining and negotiating with the European Union, candidate countries such as Serbia are required to adapt to the EU’s legal acquis in migration. It is also required to create appropriate institutional capacities and take measures to prevent illegal migrants from reaching their final destinations. For the past 15 years, the European Union has influenced Serbia to adopt several strategic documents and action plans for the first time to conduct work related to migration, border control, and human trafficking. Specific new laws, such as the Migration Management Act and the Asylum Act, were also adopted. Within the framework of pre-accession funds, the EU allocated funds for specific material equipment of border units, customs and police authorities and financed the training of members of these units to implement adopted regulations and rules. On the other hand, Serbia allocated significant resources to establishing a greater number of reception centres for migrants throughout Serbia. It also has established coordination systems and work of several state institutions in combating irregular migration. Serbia accepts and lets through all migrants who travel with appropriate documents through its territory, because they are primarily directed to more developed countries in Europe. The increased number of migrants on the territory of Serbia in the last years has also influenced an increased number of criminal acts and, consequently, a more significant number of arrested persons and filed criminal charges by state authorities. The data indicate that Serbia has an organized system combating irregular migration and security risks and threats. The conclusion is that Serbia has established appropriate mechanisms and capacities for controlling and opposing irregular migration and that, in cooperation with other European countries, it represents a stable agent of common policy in the area of migration in the region.